Industrialisation in developing countries - Akinyemi, Isaac (New York : Vantage Press, 1970)
This book examines industrialisation in developing countries with topics that include: technological education, raising capital; means of transportation; supply of water and power; basic industries; secondary industries; management; production; and marketing.
lje 1/08/2018
Loans
Keywords: Industrialization; Economic policy; Developing countries